Loss of parasympathetic innervation leads to sustained expression of pro-inflammatory genes in the rat lacrimal gland - Nguyen, Doan H. (2006)
It has been shown that removal of parasympathetic innervation to the lacrimal gland (LG) leads to rapid reduction in tear flow. Additionally, removal of the neural input resulted in disorganization of LG structure and changes in the expression of genes associated with the secretory pathway and inflammation. The goal of this study was to investigate the change in pro-inflammatory and pro-apoptotic gene expression in the rat LG following parasympathetic denervation. Male Long- Evans rats underwent unilateral sectioning of the greater superficial petrosal nerve and were sacrificed 7 days or 2.5 months later. cDNA was synthesized from LG RNA from the contralateral control (Ctla) and parasympathectomized (Px) glands and comparative real-time PCR was performed. Mean threshold cycles (MC(T)) for the Ctla and Px LG genes were normalized to 18S rRNA MC(T) values, and the relative fold change was calculated for each gene using the [Formula: see text] method. The expression of nuclear factor kappa B1, caspase 1, eotaxin, leukocyte antigen MRC-OX44, allograft inflammatory factor-1, MHC class II molecules RT.1B and RT.1D, IgG receptor FcRn, and macrophage metalloelastase was increased and remained elevated in the Px LG, compared with the Ctla LG. Increased expression of the initiator of apoptosis gene, caspase 2, was confirmed, but expression of the executor gene, caspase 6, was not elevated in the Px LG. Reduced expression of genes associated with post-translational protein processing-furin convertase, protein disulfide isomerase, and UDP-gal transporter isozyme 1-was noted in the Px LG. No significant changes in the expression of genes associated with lysosomal and non-lysosomal-mediated protein degradation were found. Removal of parasympathetic input may lead to decreased capacity for protein synthesis and elevated immune responses in the Px LG. These changes occur without increases in expression of the muscarinic acetylcholine receptor subtype 3, and may suggest the early changes in LG acinar cells and the pathophysiology of autoimmune responses.